Public perceptions of digital mental health awareness campaign in the Arab Gulf states: a qualitative thematic analysis - Noura Alomair; Ghadah Alkhaldi; Norah M. Alsadhan; Rawan Alkasabi; Samah Alageel (Frontiers in Public Health)
Mental illness is a significant public health concern and a leading cause of disability worldwide. Research shows a lack of mental health knowledge and inappropriate practices in the Gulf Cooperation Council (GCC) states. Our study aimed to evaluate individuals’ perspectives on mental health by analyzing their responses to a digital campaign directed at GCC adolescents. We conducted a qualitative thematic analysis of comments in response to the Gulf Health Council’s mental health campaign. The campaign content was shared on four social media platforms: TikTok, YouTube, Instagram, and X. A total of 2,146 comments were included in the analysis. There was a widespread denial of the existence of mental illness. The comments revealed a lack of understanding and insufficient support for individuals dealing with mental health issues. Stigma and discrimination against people with mental illness were evident in the comments. The general perception was that individuals have control over their mental health, often associating mental illness with weakness and lack of willpower. Mental illness was believed to be caused by religious and moral shortcomings, and religion was viewed as the solution. Some comments highlighted the need to acknowledge mental illness and urged the development of strategies to promote mental health. Our research shows a lack of awareness, stigma, and inadequate resources for individuals dealing with mental health issues. It highlights the importance of addressing barriers to mental healthcare and increasing access to support. Interventions focusing on stigma reduction and promoting acceptance of mental health disorders are crucial and require collaborative efforts from various stakeholders.